PERANCANGAN ULANG MACHINING FIXTURE UNTUK PRODUK CYLINDER HEAD DAN COVER CRANKCASE TIPE 168 - Asep Indra Komara (Machine : Jurnal Teknik Mesin, 2020)
The cylinder head and crankcase cover are components of an engine produced by a manufacturing company in Tangerang. Companies need to make improvements to the production process of these components in order to compete with their competitors. The improvement of the production process is done by improving the machining process stages and re-designing the engine product fixture. Actually the company already has a fixture for the engine machining process, but the fixture cannot be used to produce engine components because it still does not function properly. The problem that occurs is the deviation of the dimensions of machining results and the ineffectiveness of the machining process thereby reducing work productivity. Therefore, it is necessary to design a new fixture that is able to answer both of these problems. Fixture design through the application of the VDI 2222 method combined with the design method according to the Handbook of Jig Fixture has resulted in a fixture design and estimated new machining process time for engine components. The fixture design is then analyzed and validated using engineering software to ensure the fixture's rigidity of the clamping force, machining force, and deflection that occur during the machining process which can have an impact on dimensional deviations. Based on the results of the study conducted, a fixture design for machining cylinder head and crankcase cover products has been produced with fixture dimensions of 450 x 459 x 1125 with a weight of 190 kg. The time needed to complete the cylinder head product is 308.67 seconds and the crankcase cover is 224.19 seconds. The maximum clamping force required is 0.36 kN. Deflection that occurs in the clamping rod is 0.0048 mm, the fixture frame is 0.029 mm and the product deformation is 0.06 mm. The fixture design is expected to be able to solve the problems that exist in the company today.